The Use of Helplines and Telehealth Support in Aotearoa/New Zealand During COVID-19 Pandemic Control Measures: A Mixed-Methods Study - Pavlova, Alina; Witt, Katrina; Scarth, Bonnie; Fleming, Theresa; Kingi-Uluave, Denise; Sharma, Vartika; Hetrick, Sarah; Fortune, Sarah (Frontiers in Psychiatry, 2022)
Background: Early evidence suggests that the COVID-19 pandemic and associated interventions have affected mental wellbeing and associated health service use. Aims: the aim of this study was to examine the effect of the COVID-19 pandemic and associated public health measures on helpline and telehealth service demand. Methods: the study utilised a mixed-methods research design. Segmented regression analyses were used first to identify changes in patterns of demand for Aotearoa/New Zealand national helplines (n=11) from January 2020 until the end of March 2021. Thematic analysis of 23 in-depth interviews was used next to explore the reasons behind the quantitative findings from the perspective of various organisational stakeholders. Results: the data from 1,244,293 Aotearoa/New Zealand national helplines’ contacts between January 2020 and March 2021 showed a non-significant (1.4%) upward trend for the full range of observations. Throughout this period, a peak and trough pattern was observed. Significant demand increases were observed in anticipation of containment measures (12.4% increase from January to March 2020) and significant demand decreases coincided with relaxation of restrictions (6.9% decrease from April to June 2020). There were spikes in demand during public health interventions (i.e. mental health promotion, introduction of new helpline services) and regional lockdowns, but these did not result in significant changes in trends. In general, the demand for helplines stabilised at a new higher level. Most of the contacts occurred by telephone calls. Contacts by other methods (webchat, text, email) have shown higher uptake during the periods of lockdowns. Quantitative-qualitative data triangulation showed that youth and populations who were disproportionally negatively affected by unstable economic conditions and underemployment made more frequent contacts. Providers emphasised that increased demand could be viewed positively as a successful outcome of public health messaging; however, greater capacity is needed to better serve higher demand. Conclusions: COVID-19, related interventions, and measures of control were associated with an increase in contacts to helplines. However, the extent of the demand increases was lower than observed internationally. Moreover, in Aotearoa/New Zealand the reasons for increases in demand were often beyond the COVID-19 pandemic and measures of control.